2014
DOI: 10.1007/s13762-014-0523-1
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of Penicillium commune for bioremoval of industrial oil

Abstract: Among all environmental contaminations, industrial oil is one of the major pollutants of soil, water, and air. There are different chemical, physical, and biological methods to remove all types of oil pollutions. One of the common biological methods is to utilize the microorganisms like yeast, fungi or bacteria. Previous studies concerning the biodegradation of an aromatic compound in industrial waste water by Aspergillus niger have been reported. In this study, we tried to identify an oil-derived microorganis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Many researchers confirmed that the diversity of the fungal community is dominant among other inhabitants in the oil contamination of soils. Apparently, Aspergillus and Penicillium are the most common species in high oil-contaminated soils [53][54][55][56]. The study of actinomycetes showed that this group did not contain a large species diversity, and the group was mainly represented by the Cinereus section of the genus Streptomyces, in a minor amount.…”
Section: Resultsmentioning
confidence: 99%
“…Many researchers confirmed that the diversity of the fungal community is dominant among other inhabitants in the oil contamination of soils. Apparently, Aspergillus and Penicillium are the most common species in high oil-contaminated soils [53][54][55][56]. The study of actinomycetes showed that this group did not contain a large species diversity, and the group was mainly represented by the Cinereus section of the genus Streptomyces, in a minor amount.…”
Section: Resultsmentioning
confidence: 99%
“…2017, 9(6S), 214-226 218 biodegradation performance. The parameters involved posed a significant impact on biodegradation of pollutant [9,[21][22][23]. The optimum conditionsfor biodegradation process result in maximum pollutant degradation.…”
Section: Removal and Biodegradability Of Pah And Anthracenementioning
confidence: 99%
“…High efficiency, removal of all metals even at low concentrations, being economical, and energy independence are the main advantages of biological uptake which present this process as a viable new technology (Bai and Abraham 2002). In our previous works, the absorption of copper, nickel, and cobalt by brown algae in a fixed bed reactor showed that brown algae are capable of removing over 80 % of heavy metals from aqueous solutions (Esmaeili and Sadeghi 2014). Comparison of Cr(VI) adsorption by dried brown algae (Sargassum sp.)…”
Section: Introductionmentioning
confidence: 99%